Greek, Roman and Byzantine Pottery at Ilion (Troia) - University of Cincinnati (2007)
[Dt.:] Online-Dokument, in dem griechische, römische und byzantinische Terrakottaprodukte und Keramik mit Herkunft aus der Fundstätte von Troja gesammelt und katalogartig verzeichnet sind. - [Engl.:] Online document with Greek, Roman and Byzantine products of terracotta and pottery, which were found at the archaeological site of Troia, Turkey. The finds are compiled like in a catalogue.